R-ALE simulation of heat transfer during friction stir welding of an AA2xxx/AA7xxx joint on a large process window. (May 2019) - Robe, Hugo; Claudin, Christophe; Bergheau, Jean-Michel; Feulvarch, Eric
Highlights: The R-ALE FEM approach is capable of modeling an industrial tool. The modeling strategy quickly achieves the quasi-periodic state. A dissimilar AA2XXX/AA7XXX weld configuration is studied. The model simulates the temperature variations according to the welding parameters. Abstract: With regard to welding aluminum alloys, the control of the influence of FSW welding parameters on the failure strength of a welded joint requires the specific knowledge of the global thermal history and its impact on the evolution of the material metallurgy. The simulation of heat transfer during the welding stage is a complex problem involving a strong thermo-mechanical coupling due to the mechanical dissipation in the FSW joint. The aim of this paper is to propose: an application of the Rigid-ALE finite element approach capable of including a complex tool geometry, a modeling strategy so as to quickly obtain the quasi-periodic thermal state and a numerical approach which has the ability to treat a weld from a dissimilar 2XXX/7XXX aluminum alloy configuration. The application proposed shows that the numerical model developed is able to properly simulate the temperature evolution in accordance with the welding parameters.